GREEN FINANCE: THEORETICAL ASPECT AND FEATURES OF FUNCTIONING IN UKRAINE - SHKVARUK, Dina; DONCHAK, Lesya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the concept of "green finance", which is the concept and practice of financial instruments and resources aimed at supporting projects and initiatives that promote environmental sustainability, as well as social and economic well-being. It can cover a wide variety of financial products, from loans and investments to debt and insurance, aimed at reducing the impact of human activities on the environment. The main idea is to promote sustainable development, preserve natural resources and improve the quality of life, while ensuring economic development. The main components of the green finance structure are identified: green bonds, green loans and credits, specialized insurance services, green investment funds, financing of green startups, etc. Green loans and credits issued by banks promote energy saving projects and the use of renewable energy sources. Green bonds issued by governments and companies attract investments for environmental initiatives. Investment funds focused on green technologies and sustainable construction are characterized by specialization. Socially responsible investments include sustainability and environmental responsibility criteria. Specialized insurance products cover risks associated with climate change. Green startup financing supports the development of innovative environmental technologies. This diversity reflects the growing interest in sustainability and environmental finance. Based on the analysis, the importance of theoretical substantiation of the concept of green finance in the context of Ukraine’s European integration processes is proved. Strategies for overcoming the difficulties associated with the application of green finance in Ukraine are proposed. As for the strategies to overcome the difficulties, it is important to develop common standards and definitions for green finance, which will help to unify the understanding and application of this concept. In addition, engaging government agencies and international institutions to create a favorable legislative and regulatory environment is an important aspect. Financial barriers can be reduced through the development of incentives, subsidies, and other instruments aimed at green investments. Finally, it is important to promote education and awareness campaigns to raise awareness of the benefits and opportunities of green finance among all stakeholders.